Integrating Pd-doped perovskite catalysts with ceramic hollow fibre substrate for efficient CO oxidation. Issue 4 (August 2020) - Mahyon, Nur Izwanne; Li, Tao; Tantra, Billy Digjaya; Martinez-Botas, Ricardo; Wu, Zhentao; Li, Kang
Graphical abstract: Highlights: Pd-doped perovskite catalysts efficient for catalytic converter. Integration of perovskite catalyst into micro-structured ceramic hollow fibre without additional washcoating materials. Greater catalyst utilisation at low precious metal content. Excessive catalyst deposition created high mass transfer resistance. Abstract: Doping Pd into perovskite catalysts helps to reduce light-off temperatures, improve thermal-chemical stability and lowered catalyst cost by decreasing Platinum Group Metals (PGMs). In this study, LaFe0.7 Mn0.225 Pd0.075 O3 (LFMPO) and LaFe0.7 Co0.225 Pd0.075 O3 (LFCPO) were synthesised, characterized and evaluated for catalytic treatment of automotive emissions, using CO oxidation as the model reaction. Such catalysts were further incorporated inside micro-structured ceramic hollow fibre substrates, and compared with a packed bed configuration by light-off temperatures. Performance evaluations suggest that, LFMPO deposited inside the hollow fibre substrate could be light up at 232 °C, which is 10 °C lower than a packed-bed counterpart with the same amount of catalyst (5 mg) and GHSV of ∼5300 h −1 . While excessive incorporation of the catalyst (10 mg) generates significantly higher transfer resistance, which impairs catalytic performance of hollow fibre reactors, with CO conversion per gram of catalyst reduced from 0.01 mol g −1 to 0.0051 mol g −1 .